The Eurasian Vector of Georgia’s Political Development: Specifics and Opportunities for Implementation - Mansurov, Timur Zufarovich; Ivanov, Radmir Vladimirovich (International Journal of Criminology and Sociology, 2021)
The objective of this study is to identify the Eurasian vector of Georgia’s political development implementation features and contradictions. The possibilities and extent of Georgia’s participation in the Eurasian integration processes, as well as within various organizations (the Eurasian Economic Union, the Collective Security Treaty Organization, the Commonwealth of Independent States, etc.) are considered. The study analyzes the possibilities of Georgia’s implementation of the Eurasian development vector in political, economic, social, cultural, scientific, educational and other spheres. The potential of the Eurasian Union development as an economic organization and its attractiveness for the Georgian state is studied. It is emphasized that relations and cooperation building between Georgia and Russia and other member States of the Eurasian Economic Union is possible only subject to strengthening of the existing financial and administrative organization structures and its economic capacity building. Special attention is paid to Russia’s policy towards Georgia to attract it to integration processes taking place in the Eurasian space. The authors note the peculiarities and shortcomings of Russia’s foreign policy aimed at bringing the two states closer together, and gives recommendations for their correction. Unresolved ethnic and political conflicts and the uncertain state and administrative status of Abkhazia and South Ossetia are considered as factors that may encourage Georgia to participate and possibly join these organizations in order to resolve the existing problems. The authors of the article come to a conclusion that the Eurasian vector of political development is becoming more and more popular in Georgian society against the background of a rather distant prospect of the country’s joining the Euro-Atlantic structures, and the competition of these projects will in many ways determine Georgia’s future internal and foreign policy.